The Role of Social Media Marketing and Electronic Word of Mouth (E-Wom) in Improving Brand Image and Moisturizer Purchase Decisions Glad2Glow - Tanti Widiya; Citra Savitri; Syifa Pramudita Faddila (International Journal of Economics and Management Research, 2025)
As skincare awareness has developed, Indonesia's beauty sector has expanded quickly. With a 5.1% market share, Glad2Glow uses social media marketing to rank third among the top-selling face moisturizer brands on Shopee and Tokopedia. This research explores the influence of social media marketing and electronic word-of-mouth on purchasing decisions for Glad2Glow moisturizer, with brand image serving as an intermediary factor. A quantitative approach with a verificative design was utilized. Data collection involved distributing surveys to 150 individuals who use Glad2Glow moisturizer. Purposive sampling techniques and non-probability sampling were mixed in the sample procedure. A partial least squares (PLS) framework in conjunction with structural equation modeling (SEM) was used to analyze the data. The findings demonstrate that, when brand image mediation is applied, there is no indirect correlation. The research findings indicate that social media marketing and electronic word of mouth have a positive impact on consumer purchasing decisions. Additionally, both factors also influence brand image. However, brand image as a mediator does not facilitate the effect of social media marketing or electronic word of mouth on purchasing decisions.